Shariah Governance of Islamic Financial Institutions (IFIS): An Analysis of the Central Bank of Nigeria (CBN) Regulatory Guidelines - Abikan, Abdulqadir I.; Ahmad, Ibrahim B. (NIU Journal of Social Sciences, 2017)
Governance structure of IFIs, as provided by the Central Bank of Nigeria (CBN) guidelines, establishes two levels of Shari’ah board at the upstream and downstream of the Islamic financial industry labeled as Financial Regulation Advisory Council of Experts (FRACE) and Advisory Committee of Experts (ACE) respectively. This work examines the Shari’ah governance structure of the banking industry as laid down in the Central Bank of Nigeria’s (CBN) guidelines with the aim of determining the level of compliance with the guidelines. The work recommends that Policies need to be put in place that would ensure adequate disclosure for ease of retrieval, such as through IFIs’ websites and annual reports, fatwa and Shari’ah pronouncements and other activities of FRACE and ACE to the operative personnel of IFIs and other stakeholders. Informing IFIs stakeholders on the composition, powers, competence, and decision-making of FRACE and ACE would also enhance the transparency of the process leading to Shari’ah pronouncement. The composition of FRACE and ACE should be expanded by adding more members for developing local talents and expertise for effective governance; IFIs should focus on training and development of ACE members to avoid stagnation and obsoleteness within the industry. Keywords: Shariah, Governance, Islamic, Finance, Nigeria.